1998
DOI: 10.1046/j.1365-2044.1998.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Power spectral analysis of the electroencephalogram during increasing end‐expiratory concentrations of isoflurane, desflurane and sevoflurane

Abstract: SummaryWe studied the effects of increasing end-expiratory concentrations of isoflurane (0.3, 0.6, 0.9, 1.2 vol.%) (n ¼ 12 patients), desflurane (1.5, 3.0, 4.5, 6.0 vol.%) (n ¼ 12 patients) and sevoflurane (0.5, 1.0, 1.5, 2.0 vol.%) (n ¼ 12 patients) on power spectral analysis of the electroencephalogram (EEG). Spectral edge frequency (SEF), total power (TP) and relative power in the delta, theta, alpha and beta band were calculated. EEG changes were very similar within the three groups. SEF decreased, TP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 31 publications
3
34
0
2
Order By: Relevance
“…BIS variations are compatible with the weak sedative effect of 30% and 50% N 2 O / SEF1 and SEF2 analysis has shown higher potency density in low frequency ranges, showing that N 2 O had an important slowing-down effect in brain waves frequency. Power energy, another EEG parameter, had a statistical behavior similar to that described by other authors, who have shown an increase in PE as anesthesia goes deeper 17 . Values different than zero in burst suppression variables were not observed, showing that in such concentrations, N 2 O is unable to decrease EEG voltage amplitude to below 5 µV 18 .…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…BIS variations are compatible with the weak sedative effect of 30% and 50% N 2 O / SEF1 and SEF2 analysis has shown higher potency density in low frequency ranges, showing that N 2 O had an important slowing-down effect in brain waves frequency. Power energy, another EEG parameter, had a statistical behavior similar to that described by other authors, who have shown an increase in PE as anesthesia goes deeper 17 . Values different than zero in burst suppression variables were not observed, showing that in such concentrations, N 2 O is unable to decrease EEG voltage amplitude to below 5 µV 18 .…”
Section: Resultssupporting
confidence: 80%
“…Adjustment time for 30% and 50% FeN 2 O was established in five minutes. T h e f o l l o w i n g p a r a m e t e r s w e r e e v a l u a t e d : a ) electroencephalographic: BIS SEF1, SEF2 and power energy (PE), defined as total absolute potency measurement in the frequency range of 0.5 to 30 Hz, with variation values between 40 and 100 db 17 ; b) burst suppression (BS), defined as time percentage in the last 63 seconds in which EEG recorded amplitudes below 5 µV (low amplitude compatible with deep anesthesia) 18 ; c) hemodynamic: heart rate (HR), systolic blood pressure (SBP) and diastolic blood pressure (DBP). Lowest hemodynamic parameters levels were SBP = 80 mmHg and DBP = 60 mmHg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While P TOT has not been reported by studies investigating the EEG effects of halothane, the increase in P TOT observed with increasing halothane concentration in chickens is consistent with that reported in humans anaesthetized with isoflurane, desflurane or sevoflurane (Schwender et al . 1998). …”
Section: Discussionmentioning
confidence: 99%
“…These QEEG variables include EEG median frequency (MF; 50% quantile) (Schwilden & Stoeckel 1980, Otto et al 1996, spectral edge frequency (SEF) as the 80% (White & Boyle 1989, Otto & Short 1991, 90% (Schwender et al 1998) or 95% quantile (Hudson et al 1983, Johnson et al 1994, total power (mV 2 ) (Schwender et al 1996, Haga et al 2000, percentage distribution of total power (relative power) into the d, u, a and b frequency bands (De Beer et al 1996, Otto et al 1996 and power band ratios u/d, a/d, b/d (Schwilden & Stoeckel 1980, Haga et al 2001 derived from relative power. Reliable correlations between QEEG variables and clinical signs demonstrate that certain aspects of brain electrical activity are sensitive to the level of consciousness.…”
Section: Power Spectrum Analysis Of the Electroencephalogrammentioning
confidence: 99%